Favela, audiovisual e a CUFA: reflexões sobre 'soldado do morro', 'falcão-meninos do tráfico' e '5x favela - agora por nós mesmos' - Santos, Tiago Gomes dos (2015)
This research is dedicated to study the use of audiovisual language as an instrument of production of meaning and legitimacy of the 'locals' as the 'authentics' representatives of the slum. The music video 'Soldado do morro' (2000), the documentary 'Falcão – Meninos do tráfico' (2006) and the episode 'Arroz com Feijão' (Rice and Beans) from the movie '5 x Favela – Agora por nós mesmos' (5 x Favela – Now by ourselves) are our objects of investigation to understand how, through these audiovisual products, CUFA has reached the level of 'legitimate' representative of the slums and how this representation space can operate in the market logic.